PENGARUH KUALITAS PRODUK DAN IKLAN TERHADAP MINAT BELI ULANG MELALUI KEPUASAN KONSUMEN SEBAGAI VARIABEL INTERVENING (Studi Pada Konsumen Sabun Lifebuoy Di Kecamatan Bondowoso) - Praja, Yudha (Relawan Jurnal Indonesia, 2023)
This research aims to examine the factors that can increase the sales volume of Lifebuoy soap in the Bondowoso District, Bondowoso Regency. The study focuses on the variables of product quality, advertising, customer satisfaction as an intervening variable, and repurchase intention. The research method includes both qualitative and quantitative approaches. Qualitative data will be collected through interviews and observations, while quantitative data will be obtained from a questionnaire survey. The sample size consists of 100 respondents selected through purposive sampling. The collected data will be analyzed using the path analysis technique, preceded by instrument validity and classical assumption tests. The results of the study show that all indicators are valid and reliable based on the validity and reliability tests. The findings indicate that product quality, advertising, and customer satisfaction have a significant positive influence on repurchase intention. However, product quality does not have a significant direct effect on repurchase intention but has an indirect effect through customer satisfaction. The study suggests that improving product quality, implementing effective advertising strategies, and enhancing customer satisfaction can contribute to increasing the sales volume of Lifebuoy soap in the Bondowoso District.